THE EFFECTIVENESS OF TEACHING FOREIGN LANGUAGES THROUGH ONLINE PLATFORMS - Imomova Jasmina Sherali kizi, (TADQIQOTLAR, 2026)
This article examines the effectiveness of teaching foreign languages through online platforms in modern educational settings. The study analyzes the role of digital technologies  in  improving  students’  language  skills,  including  listening,  speaking, reading,  and  writing.  Special  attention  is  given  to  interactive  tools,  multimedia resources, and virtual communication opportunities that enhance learner engagement and  motivation.  The article  also discusses  the  advantages  and challenges  of online language instruction, such as accessibility, flexibility, technical limitations, and learner autonomy. The findings suggest that online platforms significantly contribute to the development  of  communicative  competence  when  used  appropriately  and systematically.  The  study  concludes  that  integrating  online  platforms  into  foreign language teaching can increase the overall quality and effectiveness of the learning process.